Comparison of Endodontic Retreatment in Teeth Obturated With Resilon or Gutta-Percha: A Review of Literature - Soares, Ciro (Iran Endod J, 2015)
INTRODUCTION: Retreatment of endodontically treated teeth is a challenge that requires complete removal of the previous filling material. Several techniques are indicated for this procedure. The present review tries to identify the most efficient method for extirpation of Resilon (RS) root fillings and to compare the speed and efficacy of RS and gutta-percha (GP) root filling removal. METHODS AND MATERIALS: Three trained evaluators conducted a search through three major databases (PubMed, Cochrane Library and Lilacs) over the articles published in the period from 2001 to 2014. The search keywords were Epiphany Sealer, Resilon, Retreatment and Removal Procedure. RESULTS: Twelve articles were included in the final sample (three in vitro studies and nine randomized trials). CONCLUSION: The ProTaper (manual or rotatory) system in combination with chemical solvents is the most efficient method for removing Resilon root filling. Retreatment of Resilon is more rapid and associated with less remnants of debris.